Unlocking the secrets of NPSLE: the role of dendritic cell-secreted CCL2 in blood-brain barrier disruption - Wang, Lei; Zheng, Guimin; Wang, Peiwen; Jia, Xiuchuan (Frontiers in Immunology, 2024)
Background: This study employed RNA-seq technology and meta-analysis to unveil the molecular mechanisms of neuropsychiatric systemic lupus erythematosus (NPSLE) within the central nervous system. Methods: Downloaded transcriptomic data on systemic lupus erythematosus (SLE) from the Gene Expression Omnibus (GEO) and analyzed differential genes in peripheral blood samples of NPSLE patients and healthy individuals. Employed WGCNA to identify key genes related to cognitive impairment and validated findings via RNA-seq. Conducted GO, KEGG, and GSEA analyses, and integrated PPI networks to explore gene regulatory mechanisms. Assessed gene impacts on dendritic cells and blood-brain barrier using RT-qPCR, ELISA, and in vitro models. Results: Public databases and RNA-seq data have revealed a significant upregulation of CCL2 (C-C motif chemokine ligand 2) in the peripheral blood of both SLE and NPSLE patients, primarily secreted by mature dendritic cells. Furthermore, the secretion of CCL2 by mature dendritic cells may act through the RSAD2-ISG15 axis and is associated with the activation of the NLRs (Nod Like Receptor Signaling Pathway) signaling pathway in vascular endothelial cells. Subsequent in vitro cell experiments confirmed the high expression of CCL2 in peripheral blood dendritic cells of NPSLE patients, with its secretion being regulated by the RSAD2-ISG15 axis and inducing vascular endothelial cell pyroptosis through the activation of the NLRs signaling pathway. Clinical trial results ultimately confirmed that NPSLE patients exhibiting elevated CCL2 expression also experienced cognitive decline. Conclusions: The secretion of CCL2 by dendritic cells induces pyroptosis in vascular endothelial cells, thereby promoting blood-brain barrier damage and triggering cognitive impairment in patients with systemic lupus erythematosus.